Analisis Tingkat Keramahan Lingkungan Alat Tangkap Pukat Pantai (Beach Seine) terhadap Penangkapan Ikan di Pelabuhan Pangkalan Pendaratan Ikan (PPI) Cikidang Pangandaran - Rina Madinatul Munawaroh; M.Tajuddin Noor; Exist Saraswati (Tumbuhan : Publikasi Ilmu Sosiologi Pertanian Dan Ilmu Kehutanan, 2025)
Beach seine is a fishing gear that is widely used in Indonesia, one of which is in PPI Cikidang Pangandaran. However, the effectiveness of this tool on environmental friendliness in PPI Cikidang Pangandaran is not yet known. This study was conducted to determine the level of environmental friendliness of fishing gear based on 9 criteria (CCRF) Code of Conduct for responsible fisheries FAO, 1995. The data used in this study are primary and secondary data, primary data were obtained through questionnaires distributed to fishermen who use beach seine fishing gear, while primary data were obtained from publications, books, and so on. Based on productivity data from 2017-2023, the productivity of catches in PPI Cikidang Pangandaran experienced a fluctuating pattern. In 2022, it showed the lowest productivity for the last 7 years, in 2023 it increased drastically. The results of the environmental friendliness study show that the beach seine fishing gear used in PPI Cikidang Pangandaran is less environmentally friendly. This tool has major weaknesses in the selectivity of the catch, the risk of by-catch, does not produce good quality fish.